2014
DOI: 10.2106/jbjs.m.01533
|View full text |Cite
|
Sign up to set email alerts
|

Stability Assessment of the Ankle Mortise in Supination-External Rotation-Type Ankle Fractures: Lack of Additional Diagnostic Value of MRI

Abstract: On the basis of the study results, we do not recommend the use of MRI when choosing between operative and nonoperative treatment of an SER-type ankle fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 50 publications
2
77
0
Order By: Relevance
“…Previously, an analysis of standard, non-stress radiographs alone was considered insufficient to determine the stability of the ankle mortise in patients with this type of isolated SER fracture (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). We also found that female sex and only two fracture fragments were independent factors for predicting ankle mortise stability.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Previously, an analysis of standard, non-stress radiographs alone was considered insufficient to determine the stability of the ankle mortise in patients with this type of isolated SER fracture (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). We also found that female sex and only two fracture fragments were independent factors for predicting ankle mortise stability.…”
Section: Discussionmentioning
confidence: 73%
“…The evaluator was blinded to the measurements of standard radiographs. The ankle mortise was considered unstable when the MCS was 5 mm, and at least 1 mm larger than the superior tibiotalar clear space (15).…”
Section: Radiographic Measurementsmentioning
confidence: 99%
See 3 more Smart Citations